Effect of laser focal point position on porosity and melt pool geometry in laser powder bed fusion additive manufacturing - Reijonen, Joni (Elsevier, 2025)
In laser powder bed fusion (PBF-LB) additive manufacturing (AM), the laser beam is the fundamental tool used to selectively melt metal powder layer-upon-layer to form a 3-dimensional part. Studies on the effect of the laser scanning parameters (power, speed, hatch distance, and scanning strategy in general) on part quality are abundant; however, far less emphasis has been given to the effect of the laser beam and how it is focused on the laser-material interaction plane. Here, we have studied the effect of laser beam focal point position on porosity and melt pool geometry in PBF-LB AM. In addition, we also study how the various energy density parameters developed for laser melting processes correlate with melt pool dimensions in a situation where the laser beam focal point position (and the beam diameter and laser intensity change at work plane caused by it), is taken into consideration. Furthermore, we assess the possibility of using co-axial, photodiode-based melt pool monitoring signals as a means to monitor the thermal emissions of the process, and how it correlates with the resulting melt pool geometry. It was found that melt pool penetration experiences a major decrease when the focal point position is shifted by more than ±1 mm (or 30% of Rayleigh length), which could be considered as a tolerance limit for acceptable focus shift in PBF-LB machines. Focus shifts larger than this were effectively captured by the photodiode signals, indicating the potential of using such photodiode-based melt pool monitoring systems for continuous monitoring of focus shift in PBF-LB AM. Finally, it was shown that all the studied energy density parameters, except volumetric energy density, were able to capture the trend in normalized melt pool dimensions when focus position is introduced as a variable. A new energy density metric by normalizing the melt pool monitoring signal intensity with the beam area was introduced and shown to correlate with the normalized melt pool dimensions.